Sepsis in head and neck cancer patients treated with chemotherapy and radiation: Literature review and consensus. Issue 2 (August 2015) - Mirabile, Aurora; Numico, Gianmauro; Russi, Elvio G.; Bossi, Paolo; Crippa, Fulvio; Bacigalupo, Almalina; De Sanctis, Vitaliana; Musso, Stefania; Merlotti, Anna; Ghi, Maria Grazia; Merlano, Marco C.; Licitra, Lisa; et al.
Highlights A multidisciplinary group of head and neck cancer (HNC) specialists met with the aim of reaching a consensus on the management of infections and sepsis. The Delphi Appropriateness Method was used for this consensus. External expert reviewers evaluated the conclusions according to their area of expertise. The paper contains statements about the management of septic HNC patients, which had a consensus. The paper offers a review of recent literature in these topics.